The Influence of Mastery Learning Strategy on Student Learning Outcomes in Islamic Religious Education Subjects - Ismi Siti Fauziah; Asep Tutun Usman; Iman Saifullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to determine the effect of the Mastery Learning strategy on student learning outcomes in Islamic Religious Education (PAI) in class XI-1 of SMA Negeri 1 Garut. The background of this study is based on the suboptimal student learning outcomes, which indicate that some students have not achieved the minimum mastery in PAI learning. This study involved 40 students using a stratified random sampling technique. Data were collected through questionnaires, observations, interviews, and documentation. The test results showed that the Mastery Learning strategy in SMA Negeri 1 Garut was dominated by an average positive category with an average value of 62.33 and student learning outcomes at SMA Negeri 1 Garut are dominated by a positive average category with an average value of 41.80. The results of the regression test show that the Mastery Learning learning strategy has a significant effect on student learning outcomes with a significance value of 0.005 (p <0.05). Meanwhile, the R Square value of 0.188 indicates a contribution of only 18.8%. The results of the study indicate that the Mastery Learning strategy has a positive effect on improving student learning outcomes, indicated by an increase in student understanding, attitudes, and skills after the implementation of the strategy. Thus, the implementation of Mastery Learning can be an effective alternative in improving learning outcomes in Islamic Religious Education subjects.